Development of a versatile lidar system based on passively Q-switched Nd: YAG laser for monitoring aerosols and cirrus clouds in the atmosphere - Bui, Hai Van; Dinh, Trung Van; Nguyen, Bao Thi Thanh; Vu, Oanh Thi Kim; Nguyen, Tu Xuan; Phung, Tiep Viet; Nguyen, Van Thi Khanh; Pham, Bang Dong; Pham, Tien Minh; Nguyen, Thieu Van; et al. (Communications in Physics, 2023)
Mobile lidar systems are important for sampling and monitoring over wide separated locations. In this paper, we present an in-house developed flexible and portable lidar system integrating an inexpensive passively Q-switched laser Nd:YAG and a detection module working in both analog and photon counting mode for studying the atmospheric boundary layer (BL) and cirrus clouds (CC). We developed a passively q-switched Nd:YAG pulsed laser operating at a wavelength of 532 nm with pulse energy up to 200 mJ and repetition rate of 1 Hz - 15 Hz. Our lidar system is designed to provide multi-angle lidar measurements up to 25 km. The multi-angle capability allows direct determination of the overlap function to characterize the lidar system by measuring the horizontal lidar signal. We use our lidar system to monitor the boundary layer and cirrus clouds over several locations Hanoi, Quangbinh, Danang, and Ho-Chi-Minh city. From the measurements, we derive the main properties such as the height, thickness, and optical depth of the earth’s surface aerosol layer and cirrus clouds. We demonstrate that this versatile compact and inexpensive lidar system is very useful for aerosol research and the study of high cirrus clouds.